ダイ13ジ ナンキョク チイキ カンソクタイ エットウタイ ホウコク 1972-1973 - 川口, 貞男; カワグチ, サダオ; KAWAGUCHI, Sadao (国立極地研究所, 1974)
P(論文) 1. The 13th wintering party consisting of 30 men led by the present author was in charge of research activities at Syowa Station for the period from February 1972 to February 1973. The items of the research programmes were as follows: aurora, cosmic rays, geomagnetism, ionosphere, radio physics, infrasonic pressure waves, meteorology, oceanography, seismology, glaciology, geology, geochemistry, medical sciences, balloon observation of electric field and rocket experiments for auroral studies. 2. Seven flights of sounding rockets, one is S-160 type and 6 are S-210 type, were carried out for measuring electron density, electron temperature, auroral UV, auroral X-rays, airglow, magnetic field, and ion composition. 3. Mizuho Camp (70°42'1 S, 44°17'5E) was open from the end of April to the middle of January next year. A team of 5 men led by Mr. Narita, glaciologist, was stationed there, to perform core-drilling of ice down to the depth of 150 m, micrometeorological study, and to make 6-hourly observations of surface meteorology. departmental bulletin paper